Peran Konseling Individu Dengan Teknik Cognitive Restructuring Dalam Mengatasi Inferiority Feeling Pada Penerima Manfaat Di Sentra Budi Perkasa Palembang - Dita Puspita Sari; Suryati Suryati; Hartika Utami Fitri (ScidacPlus, 2023)
ABSTRACT: This study aims to describe inferiority feelings and determine the role of individual counseling using cognitive restructuring techniques in overcoming inferiority feelings in PM with physical disabilities at the Sentra Budi Perkasa Palembang. This research is a field research using a qualitative approach. The subjects in this study were three persons with physical disabilities at the Sentra Budi Perkasa Palembangwho were taken using a purposive sampling technique. The data collection technique in this study used interview, observation and documentation techniques. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that before carrying out individual counseling using cognitive restructuring techniques, the picture of inferiority feeling in PM with physical disabilities is still very visible, marked by the PM still showing behaviors that indicate aspects of inferiority feelings such as thinking negatively about oneself. The role of individual counseling using cognitive restructuring techniques in overcomig inferiority fwwlings in PM with physical disabilities at the Sentra Budi Perkasa Palembang obtained very significant results which can be seen from the change in negative to positive behavior shown by PM with physical disabilities after counseling activities. Thus the role of individual counseling with cognitive restructuring techniques is able to overcome inferiority feelings in PM with physical disabilities at the Sentra Budi Perkasa Palembang.